Integrasi Budaya, Pendidikan, dan Politik dalam Dakwah Nahdlatul Wathan (NW) di Lombok: Kajian Biografi TGH. Zainuddin Abdul Madjid - Hamdi, Saipul (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2018)
Nahdlatul Wathan (NW) is a national religious organization that established in Lombok by Tuan Guru Haji (TGH) Muhammad Zainuddin Abdul Madjid in 1953. Although NW is the minority group in the context of national level compare to Nahdlatul Ulama and Muhammadiyah organization, but it has become the majority religious group in Lombok and noted as the most powerful and successful organization in term of religious da’wa development, education and politic. Since 1937-2018 NW has 1600 branches of madrasah and majlis ta’lim spread out all around Indonesian archipelago, including in the capital city of Indonesia Jakarta. In 2008-2018 NW took over the political authority when its leader TGH. Muhammad Zainul Majdi inaugurated as the Governor of West Nusa Tenggara province for two periods. In doing so, this article examines the way the founder of NW has carried NW into the highest achievement, especially the way TGH. Zainuddin integrates the cultural aspects such as local symbol, art, education, and politic in Nahdlatul Wathan’s da’wa activities. This research is qualitative research that data based on references. Most data are from the works of TGH. Zainuddin and any kinds of literature that especially related to him and NW.